DESAIN MEDIA PEMBELAJARAN KOMIK BERBASIS KEARIFAN LOKAL DAN PENERAPANNYA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR - Pete Era Restiani; Sukainil Ahzan; Dwi Sabda Budi Prasetya (Universitas Pendidikan Mandalika, 2015)
The research is aimed to increase students’ creativity and studenst’ achievement at the seventh grade student of SMPN 1 Praya Timur. The type of this research is classroom actions research in wich the research was conducted in two cycles. Each cycle of the research comprising of three meetings in wich two meetings were planned to have the teaching learning activities and one meeting was specified to have the evaluations of the learning process. At the first cycle, it was found that the average score of the students is 55,10 and the classical acommplishment percentage is 37,95%. Whereas in the second cycle, it was found that the average score of the students 80 in wich the acommplishment percentage is 86,20%. The score of students’ activity at the firts cycle is 3,11 wich can be catagorized into “active” category meanwhile the score of the students’ activity at the second cycle is 3,76 whic is categorized inti “very active” category. Based on the data found in the two cycle of the study, it can be concluded that The Design Of Local Wisdom Based Comic As The Learning Media Can Increase Students’ Activity And Students’ Achievment At The Seventh Grade Students Of SMPN 1 Praya Timur.